SISTEM PERAMALAN KETERSEDIAAN KERTAS STIKER MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING DARI BROWN’S - fahad, ahmad faishal (Institut Teknologi Adhi Tama Surabaya, 2023)
Smile Island Firm is a company engaged in the digital printing sector, producing stickers. The inventory of raw materials for sticker paper at this company still changes frequently due to excesses or shortages. By forecasting the availability of sticker paper using the double exponential smoothing method from Brown, Smile Island Firm can control the amount of paper sticker stock needed. This method was appropriate for forecasting the data on the availability of sticker paper production at this firm based on the closeness of the forecasting results to the actual data. The forecasting tests using α (alpha) 0.1 to α (alpha) 0 9 on raw material data for bald sticker paper production from October 2019 to September 2022 Obtained the smallest average MAPE value 4.08% at α (alpha) 0,5. Keywords: forecasting, Double Exponential Smoothing, production